2012
DOI: 10.1377/hlthaff.2012.0354
|View full text |Cite
|
Sign up to set email alerts
|

A Collaborative Accountable Care Model In Three Practices Showed Promising Early Results On Costs And Quality Of Care

Abstract: Cigna's Collaborative Accountable Care initiative provides financial incentives to physician groups and integrated delivery systems to improve the quality and efficiency of care for patients in commercial open-access benefit plans. Registered nurses who serve as care coordinators employed by participating practices are a central feature of the initiative. They use patient-specific reports and practice performance reports provided by Cigna to improve care coordination, identify and close care gaps, and address … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 17 publications
1
20
0
1
Order By: Relevance
“…In general, larger, hospital-based IDSs or physician hospital organizations have had better outcomes compared with smaller IPAs or even multispecialty group practices. 41 A recent examination of these ACOs revealed positive results of the implementation and utilization of the larger organization ACO. Although all health care costs rose over a 3-year period, the participants of the payment system had a smaller rise in costs, around $53 versus a raise of $69 for nonparticipants.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, larger, hospital-based IDSs or physician hospital organizations have had better outcomes compared with smaller IPAs or even multispecialty group practices. 41 A recent examination of these ACOs revealed positive results of the implementation and utilization of the larger organization ACO. Although all health care costs rose over a 3-year period, the participants of the payment system had a smaller rise in costs, around $53 versus a raise of $69 for nonparticipants.…”
Section: Resultsmentioning
confidence: 99%
“…44 Blue Cross Blue Shield of Massachusetts implemented a payment system paralleling an ACO payment organization in 2009, identified as an alternative quality contract, in which IDSs were measured for performance and financial benefit. 41 42 Similarly, Partners Healthcare in Boston has shown positive results of the formation and implementation of ACOs.…”
Section: Resultsmentioning
confidence: 99%
“…Of the seven relevant studies related to commissioning at individual, group and population level (Dusheiko et al 2006;Freeman and Peck 2006;Goldman 2010;Salmon et al 2012;Barnes et al 2013;Ly and Glied 2014;McLeod et al 2015), three studies described impacts on health service use, one on outcomes, one on quality and two on value for money.…”
Section: Evidence Of Impact Of Commissioningmentioning
confidence: 99%
“…A study of US managed care reported improved physician incomes and time with patients but little overall improvement in value (Ly and Glied 2014). A study of accountable care in three practices showed reduced costs and improved quality of care (Salmon et al 2012).…”
Section: Evidence Of Impact Of Commissioningmentioning
confidence: 99%
“…26 Another evaluation focusing on multiple payers in three states found increased performance on five process-of-care measures but no improvement in average blood sugar levels for patients with diabetes. 31 One study, which lacked a comparison group, found increased performance on measures of diabetes, heart failure, and coronary artery disease. 32 Patient experience surveys revealed that patients attributed to Medicare ACOs had higher increases in ratings of timely access to care and in how informed their primary care physicians were about care that their patients received from specialists, compared with beneficiaries not in ACOs.…”
Section: Recent Evaluations Of Aco Models Which Used a Range Of Methmentioning
confidence: 99%